Exploring The Teacher’s Strategies In Teaching Reading Comprehension In Senior High School - Kharimah, Iffa; Nirwanto, Rahmadi; Mirza, Akhmad Ali (Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the strategies employed by an English teacher in teaching reading comprehension to first-grade students at SMAN 6 Palangka Raya in alignment with the Merdeka Curriculum. Using a qualitative descriptive method with a phenomenological approach, data were collected through observation, interview, and documentation. The findings revealed that the teacher applied two main strategies: Digital and Multimodal Reading Strategy and Question Answer Relationship (QARs). The Digital and Multimodal Reading Strategy enhanced student engagement by integrating digital texts with images, audio, and video, allowing for deeper comprehension through multimodal input. Meanwhile, the QARs strategy guided students in identifying question types and locating answers, which fostered critical thinking and metacognitive awareness. Both strategies were found to be effective in increasing students’ motivation and understanding in reading activities. The study highlights the importance of adopting flexible and student-centered teaching approaches, especially those that align with the principles of the Merdeka Curriculum.